Aquaculture practices in the Philippines - Blanco, Billy P. (College of Fisheries, University of the Philippines, 1966)
The aim in presenting this paper is two-fold. First, to give a review account of the basic and applied knowledge of fish and shellfish culture and methods, some of which are old, and others are very recent practices learned in the Department of Inland Fisheries, College of Fisheries, University of the Philippines and observations in government and private fish and shellfish farms from 1963 to 1966; second, to make it available for future reference of educational institutions particularly among fisheries high schools, and others that are interested in the development of inland fish farming. The contents of this work includes the following scope of aquatic culture; extent if inland waters for fisheries development; fresh water pond fish farming; fish panting in streams, brooks, lakes, rivers, dams, and reservoirs; carp farming; fish culture in rice paddy, fish cultivation in bamboo fish cages; brackish water fish farming as in milkfish and mullet farming, shrimp (sugpo) cuture, oyster, kapis, tahong, (nytilus), and clams; and the role played by the Philippine Fisheries Commission, in inland fisheries development in general.